Variations of the Envelope Composition of Bacillus subtilis During Growth in Hyperosmotic Medium - López, Claudia S. (1998)
The envelope properties of B. subtilis cultures grown in LB and LBN hyperosmotic media (LB + 1.5 M NaCl) were compared. Since hypertonic cultures showed a Spo-phenotype, a Spo-mutant grown in LB was also analyzed. LBN cultures showed extensive filamentation and presented different sensitivities toward phage infection (φ29 and φ105), or antibiotics whose targets are at wall (lysozyme, penicillin G) or membrane level (polymyxin B, phosphonomycin). Results of the biochemical composition revealed that during hyperosmotic growth, the cell wall increased in thickness, and among the membrane lipids, glycolipid and cardiolipin increased in parallel with a decrease in phosphatidylglycerol. The fatty acid composition was also modified, and an increase in saturated straight chain with a decrease of saturated iso-branched fatty acids was observed. The increase of monounsaturated 18-1 (ω-9) fatty acid was probably related to the absence of sporulation observed in hypertonic media, since its increase has been shown to inhibit the KinA sensor of sporulation. The significance of the other wall and membrane composition variations (and hydrophobic surface properties) in relation to the osmotic adaptation are discussed.